Antara Maskulinitas dan Femininitas: Studi Hadis Riwayat Umar Bin Khattab (w. 23 h) Dalam Al-Kutub At-Tis’ah - Hijriyah, Aidul; Safri, Edi; Wendry, Novizal (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This research aims to represent the masculinity and femininity character of Umar bin Khattab as a hadith narrator contained in the hadith he narrated. Thus, the author is interested in examining the two characters of masculinity and femininity that are realized in the hadith and hadith narrators. The research method used in this research is socio-historical analysis (historical analysis) with the type of library research. The primary data that the author uses is al-Kutub at-Tis'ah. The initial search to collect the history of Umar bin Khattab could not look at al-Kutub at-Tis'ah because it could not detect the entire history of Umar bin Khattab. Therefore, apart from using software, the author also detected it through Ahmad bin Hanbal's Musnad book because the book was arranged with the names of friends. The secondary data are all references related to the research object such as history books, journals and so on. In the context of Umar bin Khattab, who was known as a masculine narrator, his feminine character was found. All of Umar bin Khattab's personal life, including his character or disposition, is not related to the hadith he narrated. There are two indications of Umar bin Khattab's character in the hadiths he narrated, namely based on the number of hadiths he narrated, of the 98 hadiths, 32 hadiths were found that described Umar bin Khattab's character, namely 27 hadiths that actualized masculine values and 5 hadiths that actualized feminine values, so that in the person of the narrator Umar is more dominantly masculine. And based on the 32 hadiths, there are 29 hadiths that discuss men and 3 hadiths that discuss women. The implication of the connection between Umar bin Khattab's masculinity value and the hadiths he narrated is that in terms of the narration of hadiths, Umar bin Khattab used his masculinity to spread and convey the Prophet's hadiths and did not abuse his masculinity to oppress the weak.